MSI-based polycyclic and heterocyclic aromatic hydrocarbons (PAHs and C2-DBF) in the uppermost Permian Changxing Fm. in the Meishan C section - Saito, Ryosuke; Wörmer, Lars; Taubner, Heidi; Kaiho, Kunio; Takahashi, Satoshi; Tian, Li; Ikeda, Masayuki; Summons, Roger E; Hinrichs, Kai-Uwe (In: Saito, R et al. (2022): An expanded record of proxy data in the uppermost Permian Changxing Fm. in the Meishan C section [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.952297, 2022)
A 7T solariX XR Fourier transform-ion cyclotron resonance-mass spectrometer (FT-ICR-MS) equipped with a Smartbeam II laser (Bruker Daltonik, Bremen, Germany) was used for MSI analysis. Analyses were carried out in positive ion mode in a range of 150-750 Da. A defined area of the sample was scanned by the laser with a distance of 100 µm between spots. Laser power, frequency and number of shots per spot were adjusted for optimal signal intensities. PAHs and C2-DBF were identified based on their monoisotopic mass. Internal mass calibrated results were exported from DataAnalysis 4.4. SR1 (Bruker Daltonik) and further processed in MATLAB R2015b using a DataAnalysis Script File.
Keywords: dibenzofuran; end-Permian mass extinction; FTICR-MS; Mass spectrometry imaging; Meishan; PAHs